INEXHAUSTIBLE - Fischlin, Daniel; Heble, Ajay; Melville, Lewis; Warren, Ted; Copping, Aimee (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
This piece was originally screened during IF 2022. Videography art by Aimee Copping. Vertical Squirrels is Daniel Fischlin, Ajay Heble, Lewis Melville, and Ted Warren.